2019
DOI: 10.1073/pnas.1901465116
|View full text |Cite
|
Sign up to set email alerts
|

The combination of TPL2 knockdown and TNFα causes synthetic lethality via caspase-8 activation in human carcinoma cell lines

Abstract: Most normal and tumor cells are protected from tumor necrosis factor α (TNFα)-induced apoptosis. Here, we identify the MAP3 kinase tumor progression locus-2 (TPL2) as a player contributing to the protection of a subset of tumor cell lines. The combination ofTPL2knockdown and TNFα gives rise to a synthetic lethality phenotype via receptor-interacting serine/threonine-protein kinase 1 (RIPK1)-dependent and -independent mechanisms. Whereas wild-type TPL2 rescues the phenotype, its kinase-dead mutant does not. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
(48 reference statements)
1
5
1
Order By: Relevance
“…In a recent paper 22 Although this result contrasted our expectations, it was confirmed by results obtained by the previously mentioned experimental study 22 , which suggested that the change in the expression of (table S3).…”
Section: Simulation #4: Testing Tnfα/sitpl2-dependent Synthetic Lethasupporting
confidence: 85%
“…In a recent paper 22 Although this result contrasted our expectations, it was confirmed by results obtained by the previously mentioned experimental study 22 , which suggested that the change in the expression of (table S3).…”
Section: Simulation #4: Testing Tnfα/sitpl2-dependent Synthetic Lethasupporting
confidence: 85%
“…Although these results do not entirely reflect our expectations as there are discrepancies between the in vitro experiment and our predictions, it was confirmed by results obtained in Serebrennikova et al [24] that the change in the expression of such molecules was due to the activation of feedback mechanisms. Interestingly, this result was obtained only for four out of six cancer cell lines, of which three were sensitive (HeLa, HCT116, and U2-OS), and one was resistant (CaCo-2).…”
Section: Plos Computational Biologycontrasting
confidence: 69%
“…In a recent paper, Serebrennikova et al [ 24 ] showed that TPL2 (MAP3K8) is one of the TNFα-induced cell death checkpoints. Its knockdown resulted in the downregulation of miR-21 and the upregulation of its target CASP8 (caspase-8).…”
Section: Resultsmentioning
confidence: 99%
“…4D–E ). Among the 13 genes upregulated by HOXA11-AS, tumor progression locus 2 (Tpl2, also known as COT or MAP3K8) is a hub gene of the TNF-α pathway [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%